Chlorpromazine-HCL in Acute Infantile Diarrhoea (A Brief Clinical Observation) - Pitono Soeparto; Haroen Noerasid; Liek Djupri (Paediatrica Indonesiana, 1982)
A total of 78 patients aged between 2 months aruJ 3 years suffuing from acute watery diarrhoea underwent investigation. Fifty-seven patients rectived chlorpromazinne-HCl 1 mg/kg BW/day in addition to oral glucose electrolyte solzuion. Twenty-one patimts were given a combination of chlorwomazine-HCL ( 1 mgjkg BW /day) wu/ antibiotics in additio11 to oral glucose electrolyte solution.In the first group diarrhoea stopped within 3 days in 70.4% and within 7 days in 85.2% of the treated patients. In the secoruJ group almost similar results were observed: resp. 70% and 85%. Three patients in the first group (5.3%) and 1 patient in the second group (4.8%) received i.v.f.d. because of the worsening of the diarrhoea.Side-effects observed during the study, were irritability irt one patient, heavy sedation in 2 patients and uncoordinated movements in one patient.